Penguin guano is an important source of climate-relevant aerosol particles in Antarctica - Matthew Boyer; Lauriane Quéléver; Zoé Brasseur; Barry McManus; Scott Herndon; Mike Agnese; David Nelson; Joseph Roscioli; Frederik Weis; Sergej Sel; Giselle L. Marincovich; Francisco J. Quarin; et al. (Communications Earth & Environment)
Abstract Gaseous ammonia, while influential in atmospheric processes, is critically underrepresented in atmospheric measurements. This limits our understanding of key climate-relevant processes, such as new particle formation, particularly in remote regions. Here, we present highly sensitive, online observations of gaseous ammonia from a coastal site in Antarctica, which allows us to constrain the mechanism of new particle formation in this region in unprecedented detail. Our observations show that penguin colonies are a large source of ammonia in coastal Antarctica, whereas ammonia originating from the Southern Ocean is, in comparison, negligible. In conjunction with sulfur compounds sourced from oceanic microbiology, ammonia initiates new particle formation and is an important source of cloud condensation nuclei. Dimethylamine, likely originating from penguin guano, also participates in the initial steps of particle formation, effectively boosting particle formation rates up to 10000 times. These findings emphasize the importance of ecosystem processes from penguin/bird colonies and oceanic phytoplankton/bacteria on climate-relevant aerosol processes in coastal Antarctica. This demonstrates an important connection between ecosystem and atmospheric processes that impact the Antarctic climate, which is crucial given the current rate of environmental changes in the region.